Leadership Styles and Innovative Work Behaviour: Mediated Moderation of Organizational Embodiment and Engagement - Altaf Akbar (Journal of Management Practices, Humanities and Social Sciences, 2023)
This study examines the complex relationship among inclusive leadership, resonant leadership, and innovative work behaviour in the dynamic context of Portuguese SMEs. The study based on the planned behaviour model theory, therefore, combines organizational engagement's moderating role with the supervisor organizational embodiment's mediating influence. The main objective of the study is to examine the influence of competence and leadership styles on the effectiveness of work mediated by innovative work behaviour. The data was collected through a Smart-PLS method and an extensive questionnaire filled out by 290 SME managers from Portugal. Time 1 (T1) involved a longitudinal approach that had three time periods to establish leadership and demographic baseline. Time 2 (T2) sought to understand leadership manifestations within organizational culture. Finally, Time 3 (T3) reported innovative work methods and gave a broad view of inclusive and sustainable leadership outcomes across time. It has been revealed that important creative work practices in SMEs are inclusive along with resonant leaders. Supervisor organizational embodiment is a crucial intervening variable explaining how leadership styles penetrate the fabric of organizations. In addition, creative work practices have their association changed by organization involvement; hence, it modifies such relationships between them and any given set of leadership philosophies, if any exist at all. These revelations introduce new perspectives on the intricate innovation processes.